Effects of Olmesartan, an Angiotensin II Receptor Blocker, on Peripheral Insulin Sensitivity in Japanese Subjects with Type 2 Diabetes and Hypertension - Ichimori, Shinji; Tsuruzoe, Kaku; Maeda, Takako; Kawashima, Junji; Araki, Eiichi; Goto, Rieko; Furukawa, Noboru; Nishida, Kenro; Iwashita, Shinsuke; Shimoda, Seiya; Ichinose, Kenshi (Internal Medicine, 2012)
Objective Several studies have assessed the efficacy of angiotensin receptor blockers (ARBs) on peripheral insulin sensitivity using the euglycemic hyperinsulinemic clamp technique in hypertensive subjects. However, these subjects were mostly non-diabetic, and some studies showed that ARB treatment did not improve insulin sensitivity. Thus, it is still uncertain whether ARBs could improve insulin sensitivity in subjects with hypertension and diabetes. Therefore, we evaluated the effect of olmesartan on peripheral insulin sensitivity in subjects with type 2 diabetes and hypertension using M/I value during the euglycemic-hyperinsulinemic clamp technique. Methods We enrolled 10 Japanese subjects with type 2 diabetes and hypertension who had never taken antihypertensive agents. Their blood pressure, fasting plasma glucose level, HbA1c and glucose utilization rate during euglycemic-hyperinsulinemic clamp (M/I value) were examined before and after 6 months of treatment with 10-20 mg/day olmesartan (mean: 13.0 mg/day). Results Blood pressure decreased significantly from 156/88 mmHg before starting olmesartan to 135/76 mmHg after 6 months of olmesartan treatment. The mean M/I value increased significantly from 6.33±3.19 (mg/kg/min/mU/L) × 100 to 8.11±4.20 (mg/kg/min/mU/L) × 100. Peripheral insulin sensitivity improved in eight out of ten subjects. Fasting glucose levels and HbA1c levels also decreased significantly. Conclusion These results indicate that olmesartan improves glucose metabolism by improving the peripheral insulin sensitivity in subjects with type 2 diabetes.